Komunikasi Matematis Siswa SMP dalam Menyelesaikan Soal PLSV ditinjau dari Tipe Kepribadian Extrovert dan Introvert - Nanda Sasvira Wulandari; Rooselyna Ekawati (MATHEdunesa, 2023)
Mathematical communication is necessary for students in the process of learning mathematics because through communication students can express, interpret and conclude mathematical ideas both in writing and orally. Meanwhile, the differences in personality types possessed by each student are extrovert personality types and introvert personality types. The results of the study show that (1) students with extroverted personality types tend not to include initial solutions and tend to rush when solving word problems in written mathematical communication. Whereas in oral mathematical communication, extrovert students tend not to be careful in reading the questions and tend to understand things smoothly and believe that the answers given are correct; (2) students with introverted personality types tend to be incomplete in writing down what is known and asked about the questions and tend to be careless when working on word problems because there are errors when performing arithmetic operations on written mathematical communication. Whereas in oral mathematical communication, introverted students tend to be careful and answer questions carefully by looking at the questions again. And introverted students tend to be incomplete in giving what is asked in the questions. It can be concluded that extrovert students are able to fulfill 3 indicators of written and oral mathematical communication, while introverted students are able to fulfill 2 indicators of written and able to fulfill 3 indicators of oral communication.